Autosomal dominant HK1-related neurodevelopmental disorder with visual defects and brain anomalies (NEDVIBA): An emerging mitochondrial disorder - Bobby G. Ng; Erik A. Eklund; Jill A. Rosenfeld; Abdallah F. Elias; Aya Abu-El-Haija; Celine Bris; Magalie Barth; Jong-Hee Chae; Murim Choi; Holly A. Dubbs; Carl Fratter; Nicola Foulds; et al. (Genetics in Medicine Open)
Purpose: Hexokinase 1 (HK1) encodes a ubiquitously expressed hexokinase, which is responsible for the first step of glycolysis, phosphorylation of glucose to glucose-6-phosphate. Both autosomal recessive and dominant variants in this gene have previously been shown to cause human disease, and presently, there are clinical data available for 27 individuals with the monoallelic neurodevelopmental disorder with visual defects and brain anomalies. Delineation of the entire phenotypic spectrum and genotype-phenotype relations will aid in management and counseling decisions. Methods: We present molecular and clinical data on 22 additional individuals with heterozygous, mostly de novo, variants in HK1. We also reviewed data from the published literature. Results: The clinical manifestations of neurodevelopmental disorder with visual defects and brain anomalies include varying degrees of intellectual disability/developmental delay, hypotonia, epileptic encephalopathy, visual deficits, a Leigh syndrome spectrum pattern on brain magnetic resonance imaging, and elevated lactate in blood and cerebrospinal fluid, suggesting mitochondrial dysfunction. Based on severity, individuals can be classified into mild, moderate, severe, or lethal forms. In terms of genotype-phenotype correlation, we find that all individuals carrying a missense variant at the threonine 457 residue have severe clinical features. Conclusion: HK1 should be included in mitochondrial disorder gene sequencing panels.